Age and menstrual cycle may be important in establishing pregnancy in female athletes after retirement from competition - Nose-Ogura, S.; Yoshino, O.; Kamoto-Nakamura,H.; Kanatani, M.; Harada, M.; Hiraike, O.; Saito, S.; Fujii, T.; Osuga, Y. (The Physician and Sportsmedicine, 2024)
Background Although it has been shown that amenorrhea associated with low energy availability or relative energy deficiency in sport affects body physiology in female athletes, the association between menstrual dysfunction during active sports careers and reproductive function after retirement is not clear.